Anti-ageing properties of edible bird's nest ascertained by in vitro and in vivo studies in animal model - Hou, Zhiping (2015)
According to the World Health Organization (WHO), the world average life expectancy as at 2014 is 66.26 years, having an average of 64.30 years for males and 68.35 years for females. However, the onset of menopause for women, usually around 50 years, has not been postponed along with increasing longevity, but rather brought forward due to the impacts of environment, diet, and lifestyle. Most women spend approximately one-third of their life span in the postmenopausal phase. Hormonal imbalance during menopausal stage has been linked to increased risks of the fatal diseases including Alzheimer’s disease, dementia, stroke, diabetes mellitus, and breast cancer. Hormone replacement therapy (HRT) has been used to restore postmenopausal hormonal levels in order to relieve menopausal problems, but its associated side effects including development of cancers and cardiovascular diseases have necessitated the search for other alternatives such as natural food supplementation. Edible bird’s nest (EBN) from the saliva of swiftlet has been esteemed as a precious food tonic by Chinese people since the Tang dynasty (618AD) because it contains rich amount of bioactive compounds such as water - soluble proteins, carbohydrate, iron, inorganic salt, and fiber, and is reported to traditionally possess anti-ageing, anti - cancer, and immunity - enhancing properties. Evidence-based details of its anti-ageing effects including underlying mechanisms are lacking. In this study, EBN was evaluated for its anti - ageing effects and its potential mechanisms were evaluated. First of all, ovariectomized female Sprague - Dawley rats were fed with EBN (6 %, 3 % and 1.5 % in normal pellet) for 12 weeks, then, cognitive function, metabolic indices (serum estrogen, insulin, liver enzyme, kidney function, lipid profile, and antioxidant markers) and hippocampal sirtuin - 1 protein level were in comparison with non - treated ovariectomized rats were observed, and in some instances it showed better results than estrogen therapy. Additionally, EBN produced better transcriptional regulation of hippocampal anti-oxidant genes and an Alzheimer disease isrelated genes, and hepatic insulin signaling genes. Moreover, EBN and its constituents (lactoferrin and ovotransferrin) attenuated H2O2 - induced cytotoxicity, and decreased radical oxygen species through increased scavenging activity, with corresponding transcriptional changes in anti - oxidant and apoptosis - related genes that tended towards neuroprotection. These data suggested that EBN reduced the risks of neurodegenerative diseases, and may be used as functional ingredient for the prevention of neurodegenerative and metabolism related diseases associated with estrogen deficient ageing.